INVESTIGATION OF POOR PROGNOSTIC FACTORS AMONG RHEUMATOID ARTHRITIS PATIENTS IN TURKBIO REGISTRY - Inanc, N.; Erturk, Z.; Ozen, G.; Dalkilic, E.; Koca, S. S.; Can, G.; Direskeneli, H. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS